Rancangan dan penerapan teknologi boiler vertikal fire tube untuk perebusan bubur kedelai tahu Kalisari Banyumas - Sakuri Sakuri; Hartono Hartono; Nana Supriyana; Yusmedi Nurfaizal; Reza Azizul Nasa Al Hakim (Universitas Muhammadiyah Metro, 2023)
The purpose of the study was to design and application a fire tube boiler for boiling soybean slurry in the process of making tofu with a capacity of 120 kg/day Parameters were measured to compare the boiling process of wood fuel and wood pellet boilers, the efficiency of fuel use, the improvement of tofu quality based on physical and chemical observations, and the use of water for production activities.. The boiler tube is made of steel plate with a thickness of 5 mm. 2 inch diameter sch 80 fire pipe totaling 20 rods. The boiler body is 600 mm in diameter with a height of 1600 mm. The tube sheet uses a plate thickness of 8 mm and the distance between the fire pipes 100 mm. The design uses ASME Section IV of 2004. The boiler manufacturing process uses a welding system. The test results show that the boiler was able to boil 120 kg/hour soybeans because it uses an automatic and sustainable system. The boiler is safe to use because it is equipped with a manometer and pressure control valve so that the boiler works at a safe limit below 2 bar. Boiling with a boiler produces more efficient fuel. The boiling time is faster, the quality of tofu was better chemically and physically, and the use of water in the production of tofu is more efficient.